2000
DOI: 10.1890/1051-0761(2000)010[1263:tkoial]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Knowledge of Indigenous and Local Communities: International Debate and Policy Initiatives

Abstract: This paper reviews international law and policy regarding the rights of indigenous peoples and local communities that are defining the role of traditional and indigenous knowledge in the management and conservation of biodiversity. The most influential forums occur within the United Nations system, particularly the Working Group on Indigenous Populations and the Convention on Biological Diversity. We discuss the “soft‐law” context of declarations, regional agreements, ethical guidelines, research protocols, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(74 citation statements)
references
References 3 publications
0
64
0
1
Order By: Relevance
“…Increasing access for involvement of Indigenous communities in research should also be supported. Mauro and Hardison (2000) call for scientific institutions and societies to support Indigenous community rights and development in managing their own data. In their study on traditional knowledge and science, Fernandez-Gimenez et al found that studies documenting traditional ecological knowledge (TEK) were 'less useful for the integration and application of knowledge than direct involvement by TEK holders (in this case hunters) in research and management ' (2006, p 313).…”
Section: Patterns In Responsible Community Engagementmentioning
confidence: 99%
“…Increasing access for involvement of Indigenous communities in research should also be supported. Mauro and Hardison (2000) call for scientific institutions and societies to support Indigenous community rights and development in managing their own data. In their study on traditional knowledge and science, Fernandez-Gimenez et al found that studies documenting traditional ecological knowledge (TEK) were 'less useful for the integration and application of knowledge than direct involvement by TEK holders (in this case hunters) in research and management ' (2006, p 313).…”
Section: Patterns In Responsible Community Engagementmentioning
confidence: 99%
“…A second, growing body of literature discusses the role of LTK in national and international policy (Agrawal 1995, Mauro and Hardison 2000, Berkes et al 2001b, Agrawal 2002, Memon et al 2003, Ellis 2005. For example, Satria (2007) analyses why traditional fishing practices ceased and then were reinstated in Indonesia.…”
Section: Marine Ltk As a Body Of Knowledgementioning
confidence: 99%
“…The custodianship of nature is deep‐rooted in local and Indigenous knowledge‐systems, including the intricate familiarity and connectedness of local biodiversity and ecology that nurtures responsible sustainability behaviours (CBD, 2019; Mauro & Hardison, 2000; Pascoe, 2014; Rose, 1996; UNESCO, 2017). Yet only recently has a budding section of the conservation, climate change and resource‐management community begun to recognize the gains of bridging the gap between different knowledge‐systems, the value of fostering relationships between non‐Indigenous and Indigenous scholars and practitioners and the challenges of appropriately—or the paradoxes of inappropriately—engaging local and Indigenous individuals, populations and communities in pro‐sustainability actions (Adams et al, 2014; Alexander et al, 2011; Ban et al, 2018; Brondizio & Le Tourneau, 2016; Etchart, 2017; Housty et al, 2014; Jardine, 2019; Kelbessa, 2013; Lee, Thorley, Watson, Reid, & Salomon, 2018; Lyver & Tylianakis, 2017; Mazzocchi, 2018; McLeod, Schmider, Creighton, & Gillies, 2018; Mistry & Berardi, 2016).…”
Section: Unlocking the Potential Of Actions To Bring Nature Back Intomentioning
confidence: 99%